PERIODIZATION OF TRAINING OF ATHLETICS FOR CHILDREN OF 08 TO 14 YEARS (Fiep Bulletin - online, 2013)
Today more and more children and young people are in evidence in competitive sports by participating in major competitions such as Olympics and Pan American Games, and organic growth and maturity of the child does not necessarily happen with the time schedule and their developments may be different from chronological age, different biological systems also reach the state of maturity at different times. The first manifestation of puberty in girls is usually the appearance of the breast bud or button, to 9.7 years on average, within the same year there is the appearance of pubic hair and men in the event of the first ejaculation occurs with espermarca average age of 12.8 years, the teenager at the stage of acceleration or at peak speeds of growth in stature, the periodization is a method to organize the training and there we will define those days of training strong, weak, as are the cycles of volume, repetition, series, minutes, distance, duration, which the intensity of training, cargo, strength, weight lifting, speed, for specific periods of time, which may be a week, a month or years. The early specialization, while it takes REFERÊNCIAS BIBLIOGRÁFICAS AUGUSTI, Marcelo. Treinamento de endurance para crianças e adolescentes, Revista Digital - Buenos Aires - Año 7 - N° 37 - Junho de 2001. BOMPA, Tudor O. A Periodização no treinamento esportivo. São Paulo: Phorte Editora, 2001. BOMPA, Tudor O. Periodização: teoria e metodologia do treinamento. 4 ed. São Paulo: Phorte Editora, 200 Clinica de iniciação em Atletismo. 2006, Taubaté: Confederação Brasileira de Atletismo, REINA, Jorge A. FOSS, Merle L.; KETEYIAN, J. Steven. Base Fisiológicas do exercício e do esporte. 6ª ed. Rio de Janeiro: Editora Guanabara Koogan, 2000. FILIN, V. e VOLKOV, V. Seleção de Talentos nos Desportos. Londrina: Midiograf, 1998 21º Congresso Internacional de Educação Física. 2006, Foz do Iguaçu. Descoberta de Talentos. BIBLIOGRAFIA CONSULTADA CALDEIRA, Fernando Felipe; POSSETTI, Emanuel Luiz. Atletismo Escolar. Práticas e Metodologias aplicadas ao ensino regular. Com material didático informatizado.
Keywords: Education; Maturity; Periodização; Children